The Relevance of Textual and Living Hadith Studies in Indonesia: Methodologies and Their Contributions to the Comprehension of Hadith - Darussamin, Zikri (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2025)
This study explores the relevance of textual and living Hadith approaches in Indonesia, focusing on the methods employed and their contributions to a contextual and applicable understanding of Hadith. The textual approach emphasizes a literal and scriptural interpretation of Hadith, while the living Hadith approach highlights the application and practice of Hadith in the daily lives of Muslim communities. Through a qualitative analysis utilizing historical and philosophical perspectives on various religious studies and practices in Indonesia, this article demonstrates that both approaches are complementary in enriching Islamic insight and enhancing the contextual understanding of Hadith within local settings. The findings indicate that textual studies concentrate on deriving meaning from Hadith texts based on established interpretive principles, whereas living Hadith studies investigate community practices shaped by their understanding of these texts. Living Hadith reflects an acculturation between Hadith and local culture, necessitating an interdisciplinary approach, particularly from the social sciences, to fully grasp Hadith phenomena in the Indonesian context.